Comparison of Specific Antibody, D-Phe-Pro-Arg-CH2Cl and Aprotinin for Prevention of In Vitro Effects of Recombinant Tissue-Type Plasminogen Activator on Haemostasis Parameters - Seifried, E; Tanswell, P (Thrombosis and Haemostasis, 1987)
In vitro, concentration-dependent effects of rt-PA on a range of coagulation and fibrinolytic assays in thawed plasma samples were investigated. In absence of a fibrinolytic inhibitor, 2 μg rt-PA/ml blood (3.4 μg/ml plasma) caused prolongation of clotting time assays and decreases of plasminogen (to 44% of the control value), fibrinogen (to 27%), α2-antiplasmin (to 5%), FV (to 67%), FVIII (to 41%) and FXIII (to 16%).Of three inhibitors tested, a specific polyclonal anti-rt-PA antibody prevented interferences in all fibrinolytic and most clotting assays. D-Phe-Pro-Arg-CH2Cl (PPACK) enabled correct assays of fibrinogen and fibrinolytic parameters but interfered with coagulometric assays dependent on endogenous thrombin generation. Aprotinin was suitable only for a restricted range of both assay types.Most in vitro effects were observed only with rt-PA plasma concentrations in excess of therapeutic values. Nevertheless it is concluded that for clinical application, collection of blood samples on either specific antibody or PPACK is essential for a correct assessment of in vivo effects of rt-PA on the haemostatic system in patients undergoing fibrinolytic therapy.
Keywords: rt-PA; Inhibition of in vitro fibrinogenolysis; Coagulation and fibrinolytic assays